Progressive Web Applications: Architectural Structure and Service Worker Asset Caching - Agarwal, Arush; Dixit, Akhil (International Journal of Computer Sciences and Engineering, 2019)
Progressive Web Application has emerged to be the top contender to alternative native application development. Despite the fact that the development practices for traditional applications have matured and become systemic by providing templates, cross platform development still remains a prominent topic. Developing an application with different architectural structure is redundant and comparing these on different platforms becomes demanding. PWA provides a solution to these problems by having to write a single codebase and providing similar features to all platforms with browser support. In this research paper we analyse the foundations of PWA, its features and core functionalities. A detailed investigation of the architectural structure of a PWA application and its benefit over its counterparts has been viewed. A case study analysing web applications on different platform is carried out.